Uji Pertumbuhan dan Hasil Tanaman Bayam Merah (Amaranthus tricolor L.) yang diberi Kompos Biochar dan Teh Kompos di Tanah Alfisol Semi Arid - Magdalena Hely (Fakultas Pertanian, Universitas Timor, 2022)
This study aims to determine the development of red spinach in semi-arid alfisol soil and to determine the response of plants to the application of biochar compost and biochar compost tea. This research was conducted from November 2020 to January 2021 in the experimental garden of the Faculty of Agriculture, Timor University, Sasi Village, Kefamenanu City District, North Central Timor Regency, East Nusa Tenggara Province. The design used in this study was a completely randomized design (CRD) with 2 factorials consisting of 4 replications. The first factor is the dose of biochar compost (T), which consists of 0 tons/ha (T0), 5 tons/ha (T1), 10 tons/ha (T2), 15 tons/ha (T3). The second factor is the frequency of watering compost tea (F) which consists of 0 times a week (F0), 1 time a week (F1), 2 times a week (F2), 3 times a week (F3). So the treatment combinations were: T0F0, T0F1, T0F2, T0F3, T1F0, T1F1, T1F2, T1F3, T2F0, T2F1, T2F2, T2F3, T3F0, T3F1, T3F2, T3F3 repeated 4 times so that there were 64 experimental units. The results showed that the treatment of biochar compost dose and frequency of watering compost tea on the observation of red spinach plant growth with a dose of 15 tons with a frequency of watering 2 times was able to increase plant height, stem diameter, number of leaves, total fresh weight, total dry weight, leaf fresh weight, leaf dry weight, root fresh weight, root dry weight, leaf fresh weight, leaf dry weight, leaf area and harvest index.